Case of acute drug-induced hepatitis after halothane anesthesia - I. Yu. Pirogova; Ye. V. Berestova; O. Yu. Bastrikov; Ye. B. Kovaleva; T. P. Petukhova; M. V. Guseva; I. A. Gubina; I. V. Rezepin; S. P. Sinitsyn (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To present the case of severe acute drug-induced hepatitis after halothane anesthesia in relation to significance of allergies history preoperative inquiry and assessment of medical management of patients, using modern prognostic scales.Key points. Biotransformation of volatile anesthetics can result in production of toxic metabolites and metabolic by-products, resulting in damage of the liver and kidneys. Disorders of liver function can be of two types: early – transient elevation of transaminase activity and late – liver necrosis. Mortality rate at the latter reaches 50–80%. In presented clinical case both variants developed in the same patient in different terms are described. Despite of acute drug-induced hepatitis with severe liver failure, complex treatment resulted in favorable outcome, including the remote-terms result.Conclusion. The most important factors determining favorable prognosis at drug-induced liver disease, include adequate doses of glucocorticosteroids, application of MARS-therapy and absence of background liver disease. Application of differential diagnostics algorithms and prognostic scales at drug-induced liver disease helps clinician to choose proper treatment approach at specific stage.